Histopathological Analysis of Synovial Lesions - Panage, Archana; Cherian, Susan; Naidu, Raji; Abhani, Dina (Annals of Pathology and Laboratory Medicine, 2018)
Introduction: Histopathological evaluation of synovial tissue is not routinely done for diagnosis in patients of arthritis, however it is of diagnostic value in patients, particularly if the joint involvement is monoarticular. A final diagnosis may be arrived at after considering the clinical and serological findings. Materials and Methods: We have analyzed a series of 46 cases which included 24 diagnostic biopsies and 22 cases of synovium sampled during joint replacement surgeries. Tissue was processed routinely, stained with Haematoxylin and Eosin and special stains when necessary.Histopathological findings were correlated with clinical, radiological, serological findings, TB culture and TB- PCR results wherever available. Results: We observed that knee joint was most commonly affected (73.91). Chronic non-specific inflammation was the most common histological finding seen in 15 cases (32.60%), 5 cases of which was further diagnosed as tuberculous synovitis based on, clinical and laboratory findings. This was followed by 11 cases (23.91%) of chronic degenerative osteoarthritis, nine (19.56%) cases of rheumatoid arthritis, and 5 cases (10.86%) of granulomatous inflammation. Other specific diagnosis included synovial lipomatosis, non-hemophilic hemosiderotic synovitis, synovial chondromatosis, gouty arthritis and pseudogout. In this study, we have discussed the importance of histopathological evaluation and clinical correlation in diagnosing synovial lesions. Conclusion: Histopathological findings in synovial lesions has its own limitations and may also be modified by treatment or chronicity of disease. However when correlated with clinical, serological and other investigations, it is of diagnostic importance in synovial lesions. DOI:10.21276/APALM.1651